(untitled) - Emecheta, Buchi (Đồng Nai, 2009)
When her father dies, Aku-nna and her young brother have no one to look after them. They are welcomed by their uncle because of Aku-nna's 'bride price' - the money that her future husband will pay for her. In her new, strange home one man is kind to her and teaches her to become a woman. Soon they are in love, although everyone says he is not a suitable husband for her. The more the world tries to separate them, the more they are drawn together - until, finally, something has to break.
Keywords: English language,Ngôn ngữ tiếng Anh,Short stories,Truyện ngắn; Readers,Người thích đọc sách